Penerapan Manajemen Risiko dalam Pemerintahan Negara-Negara di Asia - Rafika Ludmilla (Publikasi Indonesia, 2023)
Today risk management in Government, Federal and Local is emerging. Along with the increasing implementation of risk management concept and risk management have proven to protect many companies from the financial crisis in any decades. Asian Financial Crisis 1998-1999, Global Recession 2008, and Global Crisis 2018 deliver significant unfavorable effects to the companies, and some of the companies declared bankruptcy. Companies with effective risk management survive in any crisis since they have identified potential risks and mitigated them with the best effort. Learn from the same situation, Crisis also affected Government. Federal and Local Governments have initiated to implement risk management when managing government operations. The speed of risk implementation in government is not fast than in corporations. The research will examine and identify the implementation of risk management as an embedded process in the government or public sector. The research process will examine Asian Countries through a literature review. The sample of the Asian Population is 30% or 15 countries. The result of risk implementation in the Asian Government is varying. There are three models: formal risk management in government structure-53,33% or 8 (eight) countries has formal risk management, blended risk management – 20% or 3 countries, and ad-hoc implementation of risk management – 26,67% or 4 countries.